Empowering Health Cadres to Support Drug-Resistant Tuberculosis (DR-TB) Patient to Enroll in Treatment - Febriani, Esty; Wibowo, Adik; Kak, Neeraj; Jassim Al Mossawi, Hala (Kesmas, 2021)
Tuberculosis (TB) remains a big challenge globally, while the involvement of health cadres’ constitutes one of the key strategies for the TB program in Indonesia. These roles were further expanded to providing support to DR-TB patients. This study was a qualitative study, conducted in 2015 to explore the various factors which influence the performance of health cadres’ in supporting DR-TB patients to enroll in treatment. A total of 39 informants consisting of 24 health cadres, three nurses, four DR-TB patients, and three family members, two peer support, a head of primary health care, and two TB staffs from the District Health Office were recruited for this study. Meanwhile, a refresher training for health cadres was conducted regarding knowledge on TB, community support, effective communication, as well as patient tracing. There was no significant difference in the pre and post-test results; however the health cadres showed great capability in communicating and assessing the condition of patients. In addition, the health cadres assisted in carrying out patient tracing process, an important initial step to better understand patients' overall condition and identify problems faced while seeking treatment. Health cadres need to work with various parties such as family members, close relative to the patient, peer support groups, and nurses to encourage patients to enroll in treatment.